Chemical composition of the essential oils of four Plumeria species grown on peninsular Malaysia - Tohar, N.; Awang, Khalijah; Mohd, M.A.; Jantan, I. (2006)
The flower oils of four Plumeria L. species; P obtusa L., P. acuminata Ait. (yellow flower), P rubra L. (pink flower) and P. rubra (orange flower) hydrodistilled from samples grown on peninsular Malaysia, were analyzed by gas chromatography on two columns of different polarity and GUMS. The oil of P obtusa was found to be rich in benzyl salicylate (45.4) and benzyl benzoate (17.2), but also minute concentrations of alkanoic acids. oil obtained from, P acuminata was rich in palmitic acid (36.2), linoleic acid (16.8), lauric acid (10.4) and myristic acid (10.3). The pink flowered P rubra oil was similar to P acuminata oil in that it was also devoid of benzyl salicylate and benzyl benzoate and rich in alkanoic acids but linoleic acid was absent in the oil of the former. However, the orange flowered P rubra oil contained both the non-terpene esters (benzyl salicylate, benzyl benzoate and 2-phenylethyl benzoate) and alkanoic acids in significant amounts. The orange flowered cultivar had the highest concentration of (E) -nerolidol (14.4) and geraniol (4.1) among the species studied.